Geometrical parameter calculation of excised wheat leaves based on image analysis - ZHANG Wanhong (浙江大学学报. 农业与生命科学版)
Aiming at some deficiency of geometrical parameter calculation in plant leaves at present, we proposed a computational method suitable for measuring area, length, width and perimeter of excised wheat leaves. Wheat image was segmented under a certain background by histogram algorithm. Leaf area was calculated by statistical image number method, and leaf perimeter was calculated on the distance between adjacent pixels of the blade edge. Leaf length and width were measured by improved minimum enclosing rectangle. Then the calculated results were compared with the measured values, and statistical analysis was carried out. The results showed the calculated results were close to the measured values. The root mean square error (RMSE) values for area, length and width of wheat leaves were 0.49 cm2, 0.57 cm and 0.04 cm, respectively. The coefficient of determination (R2) for area, length and width of wheat leaves were 0.99, 0.97 and 0.96, respectively. The differences in RMSE values were close to 0 and R2 values were close to 1, and the calculated results and the measured values were insignificant, indicating that the improved algorithms for measuring area, length, width and perimeter of wheat leaves are not influenced by wheat leaf shapes, suitable for different conditions, reliable and practicable.